46 The profile and outcomes of patients referred to the national advanced heart failure outpatient clinic. (30th September 2020) - Murphy, L; Giblin, G; Tracey, C; Howley, C; Kavanagh, E; McGuinness, J; Mahon, N; Joyce, E
Abstract : Introduction: The burden of advanced heart failure (HF) is an understudied aspect of Ireland's chronic HF population. Given an expanding menu of advanced HF therapies, identifying suitable candidates for timely assessment and intervention with progression to heart transplantation or mechanical circulatory support (MCS) if appropriate, is imperative. However, given the intensity of resource and service utilization involved, contemporaneous epidemiological and descriptive data is essential for adequate resource planning and provision. Purpose: To identify demographics and outcomes of patients referred to the National Advanced HF and Cardiac Transplant centre, including identifiable markers of advanced HF according to the Heart Failure Association of the European Society of Cardiology (ESC) 2018 position statement. Methods: Consecutive patients referred to the national advanced HF clinic over a 9-month period from May 2019 to February 2020 were prospectively included in this registry. Baseline demographics, laboratory, electrocardiogram, echocardiogram parameters were recorded. Markers for advanced HF according to the ESC 2018 'I NEED HELP' criteria (table 1) were documented for each patient. Outcomes including need for admission from outpatient clinic, requirement for inotropes or subsequent MCS and/or heart transplantation and mortality were recorded. Results: A total of 32 patients were enrolled (28% female, mean age: 49 ± 12 years, 50% NYHA III or IV) over the 9-month period. The vast majority (81%, n=25) had at least one HF hospitalization in the preceding year, with 25% (n=8) having ≥ 2. Frequency of markers of advanced HF, according to the 'I NEED HELP' criteria are outlined in table 1. Notably, 69% of the cohort had ≥ 3 markers of advanced HF. At the time of clinic review, 28% (n=9) required urgent admission for further assessment and management, almost all (89%, 25% of total cohort) of these requiring inotropes. Out of the total cohort, 31% subsequently underwent MCS implantation (median: 33 ± 13 days) or heart transplantation (median 38 ± 22 days) (table 2). At time of clinic visit, 37.5% had a relative contraindication to transplantation with 16% having ≥ 2, the most frequently observed being elevated body mass index (BMI) >30 kg/m 2, excess alcohol intake and renal dysfunction with an estimated glomerular filtration rate < 30 ml/min/1.73 m 2 . Conclusion: Referrals to the National Advanced HF service in Ireland are presenting at an already markedly advanced stage, with over two-thirds having 3 or more established markers of advanced HF, a quarter requiring direct admission leading to inotropes, and almost a third proceeding to advanced surgical therapies. In addition, more than one third of patients referred had a relative contraindication identified at first consultation, with lifestyle factors accounting for a significant proportion. These findings have implications for development of formal referral pathways and greatly increased resource provision to a hitherto understudied cohort to enable optimal assessment and management for this patient group.